Analisis Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Puskesmas Sudu Kecamatan Alla Kabupaten Enrekang - Friskayanti Friskayanti; Abedneigo.C.Rambulangi; Olivia.D.Y.Pompeng (Pusat Riset dan Inovasi Nasional, 2023)
Study This aim For disclose a number of big satisfaction patient on Public health center Blade Subdistrict Alla , District Enrekang . Benefit research This is can become material reference addition For add knowledge And understanding studies about quality service , and can become material consideration for researcher other in researching relevant stuff , so produce work write more scientific complete And quality . Type research used is study descriptive For analyze quality service to satisfaction patient . Population from study This that is patient Public health center Blade Subdistrict Alla , District Enrekang whereas sample taken with technique accidental sampling ( determination without intentionally / coincidentally ) so succeed collect data with as many as 81 respondents . Technique analysis used that is use CSI formula equipped with table customer satisfaction index (CSI). Results study show that quality service to satisfaction patient on Public health center Blade Subdistrict Alla , District Enrekang enter in category very satisfied .